LuMU: desenvolvimento de um instrumento musical controlador sem fios como recurso auxiliar em sala de aula para professores de música - Alves, Francisco Breno Moura (2022)
The LuMU is a low-cost, wearable wireless controller device, in the form of gloves, with development oriented to intercommunication between devices, using Internet of Things concepts. More than an isolated device, it is a multimedia suite, composed by the integration of designed hardware and open source software. LuMU seeks to simulate the performance of a keyboard controller, with more mobility and freedom of movement. It works intuitively by touching the thumb to specific zones in other fingers of the hand, activating triggers that allow you to control specific musical notes, trigger samples (audio and video) and/or modulate sounds. It was designed to be another auxiliary tool for music teachers in the classroom environment in its various sub-areas of knowledge. In this work we developed a functional prototype, capable of intercommunication between the device and the host PC, using the OSC-over-UDP communication protocols, documentation of multimedia material to be used with the project, and the execution of tests with users.